Content of health related shaping training methodic for girls in the process of physical education - A.A. Skidan; S.V. Sevdalev; E.P. Vrublewskiy (Physical Education of Students, 2015)
Purpose: theoretical substantiation, working out and testing of health related trainings with girl students, practicing shaping in their physical education. Material: in the research 22 girl students of pedagogic specialties participated. Experiment stipulated usage of shaping methodic, based on computer program, during academic year. Results: experimental methodic of shaping permitted to bring physical condition indicators of experimental group’s girls to patterns of computer program. Analysis of the received data of body circumferential sizes did not show statistically confident distinctions from ideal patterns (р>0.05) that witness about their similarity. Results of abdomen top and bottom, torso sides and bottom of back fat folds’ measurements did not confidently differ from patterns (р>0.05). The above mentioned indicators were within normal values. With it difference for 5% of significance level was registered in the tested functional indicators of girl students, comparing with initial data. After experiment systolic and diastolic BP practically approached to normal value. Heart beats rate confidently approached to normative indicators. Conclusions: application of health related shaping methodic positively reflected on physical condition and functional state of girl students. We also proved that it was possible to use computer program for composing individualized training programs.